Endometrial gene expression in response to lipopolysaccharide between estrous cycle phases and uterine horns in cattle - Ault-Seay, Taylor B.; Payton, Rebecca R.; Moorey, Sarah E.; Pohler, Ky G.; Schrick, F. Neal; Shepherd, Elizabeth A.; Voy, Brynn H.; Lamour, Kurt H.; Mathew, Daniel J.; Myer, Phillip R.; McLean, Kyle J. (Frontiers in Animal Science, 2022)
Uterine bacterial community abundances shift throughout the estrous cycle, potentially altering the immunological environment of the uterus and impacting subsequent fertility. The objective of the current study was to evaluate the immunological impact of lipopolysaccharide (LPS), as a model for potentially pathogenic bacteria, throughout the uterine endometrium between the luteal and follicular phase of the estrous cycle. Bovine uterine tracts were harvested in mid-luteal (n = 7) or follicular (n = 7) phase. Explants were collected from the contralateral and ipsilateral horn relative to the dominant follicle or corpus luteum, then subjected to one of three treatments: uncultured control, cultured control, or cultured with LPS (1 µg/mL). Explants underwent RNA extraction and targeted RNA sequencing for expression analyses of 40 immune response related genes. Sequencing reads were mapped to Bos taurus genome in CLC Genomics Workbench. Resulting total read counts were normalized by housekeeping gene GAPDH and analyzed for overall expression profile by Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) and Variable Importance in Projection (VIP) analyses in Metaboanalyst. Individual gene expression differences were determined by GLIMMIX procedure in SAS with fixed effects of treatment, estrous phase, uterine horn, and their interaction, with random effect of individual uterus. Expression of 29 genes were affected among treatment groups, with seven genes increased in LPS treatment compared to other groups (P < 0.05). Multiple genes were affected by estrous phase and uterine horn, independent of treatment (P < 0.05). The OPLS-DA analyses indicated overall gene expression differences due to clustering by estrous cycle and treatment (P < 0.001), with no effect of uterine horn (P > 0.10). Similar clustering was observed between luteal and follicular phase explants of controls, but distinct separate clustering between phases with LPS treatment (P = 0.001). According to VIP analyses, mucins were identified as contributing the most to differences observed between phase and treatment. In conclusion, estrous cycle phase resulted in differing overall endometrial gene expression profiles of immune response to LPS treatment. Therefore, altered immunological environment of the uterus in response to bacteria at different estrous cycle stages may lead to differences in reproductive success.